1998
DOI: 10.5326/15473317-34-3-260
|View full text |Cite
|
Sign up to set email alerts
|

Triple pelvic osteotomy: effect on limb function and progression of degenerative joint disease

Abstract: The objective of this study was to evaluate prospectively the outcome of 21 clinical patients treated with triple pelvic osteotomies during the year following surgery. Specific aims included documenting the time of and extent of improved limb function as measured by force plate analysis, evaluating the progression of degenerative joint disease (DJD) in the treated and untreated coxofemoral joints, and determining whether or not triple pelvic osteotomy resulted in degenerative joint changes in the ipsilateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 9 publications
4
48
2
5
Order By: Relevance
“…While Johnson et al (1998), have reported that the degeneration in the joint continued even a�er TPO, Wallace and Olmstead (1995) state the opposite. The fact that, with the exception of 2 of our cases, we did not encounter such complications, is parallel to the view of Wallace and Olmstead (1995).…”
Section: Discussionmentioning
confidence: 99%
“…While Johnson et al (1998), have reported that the degeneration in the joint continued even a�er TPO, Wallace and Olmstead (1995) state the opposite. The fact that, with the exception of 2 of our cases, we did not encounter such complications, is parallel to the view of Wallace and Olmstead (1995).…”
Section: Discussionmentioning
confidence: 99%
“…a-Acetabulum'un ön ve arka köşelerini birleştiren hattın ortasından caput femoris'in merkezine dik olan uzaklık, b-Acetabulum'un ön ve arka köşelerini birleştiren hattın ortasından caput femoris'in dış noktasına dik uzaklığı Dogs with hip dysplasia are generally described as having trouble walking upstairs, bunny happing, standing up with difficulty and showing a laxity of the hip joint. It is also reported that laxity of the hip joint is established in the case of a positive Ortolani test, while a negative test does not indicate that the hip is healthy because of the occasional false positive and false negative results 11,17,18 . Similar clinical results were found in all dogs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain desired results with TPO, patient should be young and free from degenerative changes of the hip joint, or at the very least with only a minimal level of such changes 11,12 . All dogs in this study had no clinical and radiological finding related with hip joints at the beginning of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora existam vários estudos que descrevam a análise da locomoção de cães com DCF através do uso da plataforma de força (BENNETT et al, 1996) e após vários tratamentos: osteotomia pélvica tripla (MAC LAUGHLIN et al, 1991;JOHNSON et al, 1998;MANLEY et al, 2007;), prótese de quadril (DUELAND et al, 1977;ANDERSON et al, 1988;BUDSBERG et al, 1996), sinfisiodese púbica juvenil (MANLEY et al, 2007) e osteotomia de cabeça e colo femoral (DUELAND et al, 1977 Os tratamentos cirúrgicos mais recomendados para articulações coxofemorais com artrite severa são a osteotomia da cabeça e colo femoral, ou a substituição total da articulação coxofemoral. Para animais cujo, diagnóstico de DCF é feito em estágio inicial, antes de instalação da osteoartrite secundária são recomendados procedimentos profiláticos como a osteotomia pélvica tripla e a sinfisiodese púbica juvenil.…”
Section: Lista De Apêndicesunclassified